2022
DOI: 10.3389/fphar.2021.808867
|View full text |Cite
|
Sign up to set email alerts
|

San-Huang-Yi-Shen Capsule Ameliorates Diabetic Nephropathy in Rats Through Modulating the Gut Microbiota and Overall Metabolism

Abstract: San-Huang-Yi-Shen capsule (SHYS) has been used in the treatment of diabetic nephropathy (DN) in clinic. However, the mechanisms of SHYS on DN remain unknown. In this study, we used a high-fat diet (HFD) combined with streptozotocin (STZ) injection to establish a DN rat model. Next, we used 16S rRNA sequencing and untargeted metabolomics to study the potential mechanisms of SHYS on DN. Our results showed that SHYS treatment alleviated the body weight loss, hyperglycemia, proteinuria, pathological changes in kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…Christensenellaceae _R-7_group, Clostridia_UCG-014 and Parasutterella were all increased in the combined treatment group. Evidence showed that Christensenellaceae _R-7_group was increased with a special traditional Chinese medicine capsule intervention, which could ameliorated hyperglycemia and pathological changes in diabetic nephropathy in rat models ( Su et al, 2021 ). Clostridia_UCG-014 was identified as a probiotic associated with tryptophan metabolism in colitis mice and might mediate the improvement of gut barrier disruption, colon inflammation and the pathological phenotype ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Christensenellaceae _R-7_group, Clostridia_UCG-014 and Parasutterella were all increased in the combined treatment group. Evidence showed that Christensenellaceae _R-7_group was increased with a special traditional Chinese medicine capsule intervention, which could ameliorated hyperglycemia and pathological changes in diabetic nephropathy in rat models ( Su et al, 2021 ). Clostridia_UCG-014 was identified as a probiotic associated with tryptophan metabolism in colitis mice and might mediate the improvement of gut barrier disruption, colon inflammation and the pathological phenotype ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous supplementation of L-proline can enhance the antioxidant capacity of rats [ 34 ]. The results of metabonomics showed that proline metabolism was disordered, and excessive production of ROS caused by downregulation of proline would lead to intracellular damage of biomolecules, including cell cycle blocking, autophagy and apoptosis [ 35 ]. HMOX1 is a downstream target gene of HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical resveratrol treatment significantly reduced body and kidney weights but not the fasting blood sugar (FBS) of db/db mice, which were associated with the decrease in the F/B ratio after resveratrol treatment ( Cai et al, 2020 ). Qing-Re-Xiao-Zheng formula ( Gao Y. et al, 2021 ), Cordyceps cicadae polysaccharides ( Yang J. et al, 2020 ), and San-Huang-Yi-Shen capsule ( Su et al, 2022 ) significantly lowered serum glucose and the ratio of Firmicutes -to- Bacteroidetes in mice with diabetic kidney disease. While treatment with QiDiTangShen granules and Tangshen formula had no significant effects on the F/B ratio in db/db mice, this maybe partly explains why they do not alter body weight and glycemic levels in those mice ( Zhao et al, 2020 ; Wei et al, 2021 ).…”
Section: Animal Studies Of Natural Products For the Treatment Of Ckd ...mentioning
confidence: 99%